Strategi Guru Agama Hindu dalam Menumbuhkembangkan Sikap Moderat Siswa di SD Saraswati 6 Denpasar - Darma Permana, I Dewa Gede (Jurnal Penelitian Agama Hindu, 2024)
The heterogeneous patterns of some schools in Indonesia are prone to create an attitude of intolerance. Therefore, Hinduism teachers at Saraswati 6 Elementary School in Denpasar implement strategies aimed at developing moderate attitudes in students. On the basis of these problems, this research is present to dissect the form and implications of the Hindu religious teacher's strategy in more depth. This research uses a qualitative method with a descriptive naturalistic approach, where the data collection process is carried out through observation, interview, literature study, and documentation study techniques. The data is then processed using the Miles and Huberman analysis technique to obtain valid research results. The results of this study show that, the strategy of Hinduism teachers in developing moderate attitudes of students at Saraswati 6 Elementary School in Denpasar is poured specifically and systematically through three stages of learning, namely: 1) The learning planning stage, where teachers focus on self-briefing that contains the concept of religious moderation. 2) The learning implementation stage, where teachers focus on creating an inclusive learning atmosphere, such as routinely singing national compulsory songs, using cooperative learning models intensely, and actively inserting the concept of Religious Moderation in Hindu teachings, 3) The learning evaluation stage, where teachers use observation techniques to determine the extent of the development of students' moderate attitudes. The conclusion of this research is something that is important to be applied by teachers and schools as a guide in creating a school environment that is harmonious in the midst of diversity.